Consumer purchase intention on buying organic skin care products in Malaysia / Puteri Afiqah Auni Abdullah - Abdullah, Puteri Afiqah Auni (Faculty of Business and Management, 2018)
This study examines on consumer purchase intention on buying organic skin care products in Malaysia. The independent variables that are used in this study are attitude, subjective norm, perceived behavior control, consumer values and past experiences with organic skin care products. The results were collected from 389 numbers of respondents through a questionnaire. A survey consisting of 49 questions that uses a Likert Scale questions to establishing measurable values from the respondents. The data analysis intends to determine whether there are significant effect between the independent variables (attitude, subjective norms, perceived behaviour control, consumer values and past experiences with organic skin care products) with the dependent variable (consumer purchase intention on buying an organic skin care products). This study found that there were only four from the independent variables (attitude, subjective norms, consumer values and past experiences with organic skin care products) has significant effect where by only one independent variable (perceived behavior control) has insignificant effect with the dependent variable (consumer purchase intention on buying an organic skin care products). The most significant predictor variable of consumer purchase intention towards organic skin care products is attitude with highest Standard Coefficient Beta value is 0.560 with p-value of 0.000.